The Power of Digital Media: Instagram and the Distribution of Kebaya Designs - Agista, Tan Paulina Candra; ., Faruk; Handajani, Suzie (KnE Social Sciences, 2019)
The world has witnessed many changes including the use of media. In this third millennium period, new media plays a major roles in distributing news and advertisement. The emergence of digital media such as Instagram has changed the traffic of photos, videos, and stories distribution. Due to its speed, Instagram has been chosen by many people as an effective media tool. Anne Avantie, an Indonesian kebaya designer has used Instagram for introducing, distributing, and advertising her kebaya designs. This paper intends to present the discussion on how Instagram works towards the distribution of Avantie’s kebaya designs and how it contributes to Avantie’s domination in the field of fashion. Walter Benjamin’s theory about the mechanical reproduction and Douglas Davis’s concept of the digital reproduction are used to examine the effect between Instagram and the distribution of Avantie’s kebaya designs. To achieve its objective, this project applies a qualitative method. The finding reveals that Instagram has multiple functions in the field of fashion and it contributes much towards Avantie’s fame and success. Keywords: Instagram, distribution, kebaya designs